Synergistic Effect of Banaba Leaf Extract and Policosanol (Raydel®) Ameliorate High Cholesterol and High Galactose-Diet Induced Adverse Events in Zebrafish - Kyung-Hyun Cho; Sang Hyuk Lee; Yunki Lee; Ashutosh Bahuguna; Ji-Eun Kim; Krismala Djayanti; Cheolmin Jeon (Pharmaceuticals)
Background: This study aimed to explore the therapeutic potential of a dietary regimen of banaba leaf extract (BNB), policosanol (PCO, Raydel®), and their combination (BNB+PCO), to mitigate high cholesterol (HC) and high galactose (HG) diet-induced dyslipidemia, hyperglycemia, oxidative stress, senescence, and organ damage in zebrafish (Danio rerio). Methodology: Zebrafish (n = 28/group) were fed with HC (4% w/w)+HG (30% w/w) or HC+HG supplemented either with BNB (0.1% w/w) or PCO (0.1% w/w) or BNB+PCO (0.1% w/w each). Following 6 weeks of dietary intervention, biochemical and histopathological examinations across the groups were performed. Results: Post 6 weeks of consumption, the BNB+PCO group exhibited a significant 40% decrease in body weight (BW) relative to the BW of the HC+HG group, while the BNB or PCO groups displayed nonsignificant changes in BW. Both BNB and PCO reduced HC+HG-induced dyslipidemia and hyperglycemia; however, co-administration (BNB+PCO) demonstrated a significantly greater therapeutic effect in countering these conditions compared to either BNB or PCO alone. A similar effect of the BNB+PCO combination was observed on the elevation of plasma sulfhydryl content, paraoxonase (PON), and ferric ion reduction activity (FRA), with notably ~1.2-times (p < 0.01) higher levels compared to their corresponding values observed in the BNB or PCO groups. Significantly diminished plasma AST, ALT, hepatic interleukin 6 (IL-6) levels, and fatty liver changes were observed in response to BNB+PCO, compared to either BNB or PCO alone. Also, BNB+PCO displayed a higher curative effect against HC+HG-induced impairment of tissue regeneration than BNB or PCO alone. A notable effect of BNB+PCO was perceived in protecting kidneys, testis, and ovary damage. Consistently, BNB+PCO showed a profound impact on mitigating HC+HG elevated reactive oxygen species (ROS) generation, apoptosis, cellular senescence, and accumulation of brain-binding lipid proteins (BLBPs) and 4-hydroxynoneal (4-HNE) in the brain. Conclusions: The findings highlight the synergistic effects of the BNB and PCO combination to mitigate the adversity posed by the consumption of the HC+HG diet.